Local Government Capital Expenditure, Internal Supervision, Wealth and Human Development: Evidence from Indonesia - Jopinus Saragih (Jurnal Dinamika Akuntansi dan Bisnis, 2022)
This study examines the influence of local government capital expenditures, internal supervision, and wealth on human development in Indonesian local governments. Using secondary data from the authorized government institutions from 2017 to 2019, a set of unbalanced panel data with total 1,437 observations was generated. Using panel data regression analysis, this study discovers that local governments in Java, Bali and Sumatra have a better human development achievement, followed by Kalimantan, Sulawesi, and Eastern Indonesia. City local governments also have a higher average of human development index achievement than regency local governments. Further, we find that local government capital expenditures and internal supervision positively affect human development, while local government wealth has insignificant effect on human development. Our findings imply that local governments are suggested to increase the amount of capital expenditures for infrastructure development, especially for local governments that are relatively underdeveloped in Indonesia.